Blackening Song - Thurlo, Aimee; Thurlo, David (New York FORGE, 2001)
FBI agent Ella Clah returns to her Navajo reservation to find the killer of her father, a Christian minister. The probe is complicated by her long stay in the white world. While she is convinced that she has retained her Indian soul, the locals don't think so. By the authors of Second Shadow.
"A Tom Doherty Associates book."
87509
Keywords: Clah, Ella (Fictitious character) -- Fiction; Police -- New Mexico -- Fiction; Navajo Indians -- Fiction; Navajo women -- Fiction; New Mexico -- Fiction; Mystery fiction